Analyzing User Intention to Adopt Balinese Script Digital Tool: A Technology Acceptance Model Approach - Cokorda Pramartha; Madek Jeani Purnama; Ida Bagus Ary Indra Iswara; I Putu Gede Hendra Suputra; I Wayan Arka; Ni Luh Watiniasih (Journal of Information Systems Engineering and Business Intelligence, 2026)
Background: Digital tools can help local scripts remain visible and usable in everyday communication. For that to happen, however, the tools must be accepted by users, not merely made available. In the case of Balinese script, evidence on what encourages people to use digital writing tools is still limited, particularly in relation to perceived usefulness and ease of use. Objective: This study examined the factors that influence users’ intention to adopt the Balinese Script Keyboard. Analyses were made based on the Technology Acceptance Model, more specifically, Perceived Usefulness and Perceived Ease of Use. Methods: A typing task followed by a questionnaire was conducted with 109 respondents in Bali. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) in SmartPLS. The aspects on which the analysis was built are measurement-model assessment, covering reliability, convergent validity through average variance extracted (AVE), and discriminant validity, followed by structural-model testing using bootstrapping. Results: Respondents in general showed positive perceptions of the keyboard, with construct mean scores of 5.29 for PU, 5.26 for PEOU, and 5.32 for Usage Intention (INT). The measurement model met the required validity and reliability criteria, with outer loadings ranging from 0.872 to 0.994, AVE values from 0.826 to 0.974, and Cronbach’s alpha values from 0.958 to 0.987. The structural model also supported all proposed relationships. A significant positive effect on INT was found with PU (β = 0.513, t = 21.787, p < 0.001); similarly, PEOU also had a significant positive effect on INT (β = 0.537, t = 20.724, p < 0.001), and lastly, PEOU had a strong positive effect on PU (β = 0.743, t = 15.413, p < 0.001). 96.0% of the variance in INT and 54.7% of the variance in PU could all be explained by the model. Conclusion: The findings show that perceived usefulness and perceived ease of use both shape the users’ intention to adopt the Balinese Script Keyboard. Other than that, ease of use also correlates strongly with perceived usefulness by strengthening it, suggesting that usability is a key factor in the acceptance of digital tools for complex traditional scripts. This study provides early empirical support for the application of TAM to minority-script digital technologies. It is noted that broader user groups, additional adoption factors, and examination of longer-term use in real-world settings are all to be included in future research.   Keywords: Balinese script digital tool, Technology acceptance model, Perceived Usefulness, Perceived Ease of Use, Usage Intention